Bacterial Zombies And Ghosts: Production Of Inactivated Gram-Positive And Gram-Negative Species With Preserved Cellular Morphology And Cytoplasmic Content - Taddese, Rahwa; Belzer, Clara; Aalvink, Steven; De Jonge, Marien I; Nagtegaal, Iris D; Dutilh, Bas E; Boleij, Annemarie (bioRxiv, 2018)
There are many approaches available to inactivate bacteria, each with a different efficacy, impact on cell integrity, and potential for application in high-throughput. The aim of this study was to compare these approaches and develop a standardized protocol for generation of intact Gram-positive as well as on Gram-negative "bacterial zombies", i.e. cells that are metabolically dead with retained cellular integrity. Here, we introduce the term "bacterial zombies" in addition to "bacterial ghosts" to differentiate inactivated bacteria with preserved cellular integrity from those with perforated membranes, where DNA and cytoplasmic contents have been released. This differentiation of inactivated bacteria is important if the cell content is the subject of study, or if cell contents in the media may cause unwanted effects in downstream applications. We inactivated eight different bacterial species by treatment with beta-propiolactone, ethanol, formalin, sodium hydroxide, and pasteurization. Inactivation efficacy was determined by culturing, and cell wall integrity assessed by quantifying released DNA and visualization by scanning electron microscopy. Based on these results, we discuss the choice of bacterial inactivation methods, and conclude that beta propiolactone and ethanol are the most promising approaches for standardized generation of bacterial zombies.